Brazilian studies in philosophy and history of science an account of recent works - Krause, Décio; Videira, Antônio Augusto Passos; SpringerLink (Online service). (Dordrecht New York Springer, 2011)
This volume, "The Brazilian Studies in the Philosophy and History of Science", is the first attempt to present to a general audience, works from Brazil on this subject.
This volume in the Brazilian Studies in the Philosophy and History of Science is the first attempt to present to a general audience some works which have been done in Brazil on ths subject. The included papers are original, reaching a remarkable number of relevant topics of philosophy of science, logic and on the history of science. The Brazilian community has increased in the last years in quantity and in quality of the works, most of them being published in respectable international journals on the subject. There is an informal but general among the philosophers and historians of science that the works must be of high quality, and we hope this volume may contribute to widespread this idea. The chapters of this volume are forwarded by a general introduction, which aims at to sketch not only the contents of the chapters, but it is conceived as a historical and conceptual guide about the development of field, as developed in Brazil. The introduction intends to be be very useful to the interestes readers, and not only to the specialists helping them to evaluate the production of this country that it is raising up in the international context
Preface - D. Krause & A. A. P. Videira - Introduction by Michel Paty Newton and Inverse Problems - Andre K. T. Assis The metaphysics of non individuality - Decio Krause Einstein, Godel, and the mathematics of time - Francisco A. Doria & Manuel Doria A contemporary view of population genetics in evolution, Joao Carlos M. Magalhaes & Cedric Gondro On the Nature of Mathematical Knowledge, Jairo Jose da Silva The etiological approach to the concept of biological function, Karla Chediak Echoes from the past: the persisting shadow of classical determinism in contemporary health sciences, Kenneth Rochel de Camargo, Jr. Natural Kinds as Scientific Models, Luiz Henrique Dutra Regeneration as a Difficulty for the Theory of Natural Selection: Morgan's Changing Attitudes, 1897-1932, Lilian Al-Chueyr Pereira Martins Sciences in Brazil: an overview from 1870 - 1920, Dantes, Maria Amelia, Figueiroa, Silvia & Lopes, Maria Margaret Functional explanations in biology, ecology, and Earth system science: Contributions from philosophy of biology, Nei Freitas Nunes-Neto and Charbel Nino El-Hani Continuity and change: charting David Bohm's evolving ideas on quantum mechanics, Olival Freire Junior The Causal Strength of Scientific Advances, Osvaldo Pessoa Jr. Galileo and Modern Science, Pablo Ruben Mariconda Human Evolution: Compatibilist Approaches, Paulo C. Abrantes Isaac Newton, Robert Hook, and the mistery of orbit, Penha Dias & Teresinha J. Stuchi Freudian Psychoanalysis as a Model for Overcoming the Duality Between Natrual and Human Sciences, Richard Theisen Simanke Henri Becquerel and radioactivity: a critical revision, Roberto de Andrade Martins On Darwin, Knowledge and Mirroring, Renan Springer de Freitas The qualitative analysis of differential equations and the development of dynamical systems theory, Tatiana Roque Contextualizing the Contexts od Discovery and Justification: How to do Science Studies in Brazil, Antonio A. P. Videira & Andre L. de O. Mendonca Quasi-Truth and Quantum Mechanics, Newton da Costa & Otavio Bueno
Includes bibliographical references and indexes
Electronic reproduction.
Keywords: Science -- History; Science -- Philosophy -- History